Comparison of Neutron Organ and Effective Dose Coefficients for PIMAL Stylized Phantoms in Bent Postures in Cranial and Caudal Irradiation Geometries. Issue 5 (May 2021) - Sivabhaskar, Sruthi; Perry, Alexander; Dewji, Shaheen
Abstract : Abstract: Radiation dose estimations in the human body are performed using computational reference phantoms, which are anatomical representations of the human body. In previous studies, dose reconstructions have been performed focusing primarily on phantoms in an upright posture, which limits the accuracy of the dose estimations for postures observed in realistic work settings. In this work, the International Commission on Radiological Protection (ICRP) Publication 103 recommendations for monoenergetic neutron plane sources directed downward from above the head (cranial) and upward from below the feet (caudal) for adult female and male reference phantoms were used to calculate organ absorbed and effective dose coefficients. The Phantom with Moving Arms and Legs (PIMAL) and the Monte Carlo N-Particle (MCNP) radiation transport code were used to compute organ-absorbed dose and effective dose coefficients for the upright, half-bent (45°), and full-bent (90°) phantom postures. The doses calculated for each of the articulated positions were compared to those calculated for the upright posture by computing the ratios of the coefficients (45°/upright and 90°/upright). These ratios were used to assess the effectiveness of upright phantoms in providing a comparable estimate when conducting dose estimations and dose reconstructions for articulated positions. This work compiling neutron cranial and caudal posture-specific dose coefficients completes the series of dose coefficients computed for posture-specific ICRP Publication 116 irradiation geometries for monoenergetic photons and neutrons, in addition to cranial and caudal monoenergetic photons. Results reported demonstrated that organ-absorbed dose coefficients for most of the organs in the CRA and CAU irradiation geometries were significantly higher for the bent phantoms than for the upright phantom. Since the upright phantom underestimates the organ-absorbed dose, this demonstrates the impact of posture while performing dose calculations. Organ doses reported in past neutron dose coefficient data were found to omit effects from neutron resonances at energies of 0.435, 1.0, and 3.21 MeV from 16 O in tissue. Reported data notes as high as 60% underestimation for neutron organ-absorbed doses, specifically at the neutron resonance energy region omitted by smoothing. Ongoing studies are examining the effect of resonances on reported neutron organ-absorbed dose coefficients in ICRP 116 geometries. Abstract : Supplemental digital content is available in the text.